Concepts of Happiness and Well-Being in Social and Behavioral Sciences - Jugović, Aleksandar; Bogetić, Dragica; Živaljević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The aim of the paper is a scientific analysis of the terms and concepts of subjective well-being, happiness, and quality of life, and their significance for the social and behavioural sciences, through the application of analysis and synthesis of empirical and theoretical findings as general methods used in the work. In addition, the paper analyzes empirically validated correlates and outcomes of subjective well-being, as well as two theoretical postulates that define the preconditions of well-being – the theory of satisfying needs and the theory of hedonism. The importance of concepts of wellbeing for behavioral sciences can be seen in the benefits of happiness at the individual and wider social level. Gains at the individual level are reflected in the results of numerous studies that show happiness (satisfaction with life, positive feelings and low levels of negative feelings) and success in different living domains in a positive correlation, including health, partnership and social relationships, income, work performance, and prosocial behavior. Through the concluding observations of individual studies that high levels of one's people's subjective well- being can lead to a more stable and productive society as a whole, the wider profit of the system from work on improving the subjective well-being of one nation is reflected.